Gamma delta T cells in non‐immune patients during primary schistosomal infection. Issue 1 (16th May 2014) - Schwartz, Eli; Rosenthal, Etti; Bank, Ilan
Abstract The mevalonate pathway is critical for the survival of Schistosoma. γδ T cells, a small subset of peripheral blood (PB) T cells, recognize low molecular weight phosphorylated antigens in the mevalonate pathway, which drive their expansion to exert protective and immunoregulatory effects. To evaluate their role in schistosomiasis, we measured γδ T cells in the PB of non‐immune travelers who contracted Schistosoma hematobium or Schistosoma mansoni in Africa. The maximal level of γδ T‐cells following infection was 5.78 ± 2.19% of the total T cells, versus 3.72 ± 3.15% in 16 healthy controls [P = 0.09] with no difference between S. hematobium and S. mansoni in this regard. However, among the nine patients in the cohort who presented with acute schistosomiasis syndrome (AS), the level (3.5 ± 1.9%) was significantly lower than in those who did not (8.6 ± 6.4%, P < 0.05), both before and after therapy. Furthermore, γδ T cells increased significantly in response to praziquantel therapy. In a patient with marked expansion of γδ T cells, most expressed the Vδ2 gene segment, a hallmark of cells responding to cognate antigens in the mevalonate pathways of the parasite or the human host. These results suggest an immunoregulatory role of antigen responsive γδ T cells in the clinical manifestations of early schistosomal infection.